Social-economic inequalities in the Russian society: Public perception and its dynamics - S. V. Mareeva (RUDN journal of Sociology, 2025)
The article, based on the empirical data of all-Russian surveys conducted by the Institute of Sociology of the FCTAS RAS, explains the dynamics of the public perception of social-economic inequalities over the past decade. The relevance of the research question is determined by the impact of inequality on the country’s sustainable development and public behavior. The author shows that the perception of inequalities in the Russian society in the 2020s has changed, but this dynamic differs for assessments of inequalities in general and of their impact on one’s life situation. In the first case, the views of Russians are more homogeneous and are characterized by an acute perception (despite some changes in recent years) of inequalities in society, regardless of their own situation. In the second case, Russians’ views to a greater extent depend on the personal objective situation and subjective well-being, and inequalities are perceived less painfully. In both cases, income inequality comes first due to being considered not only high but also unfair, although there are some positive changes. Among non-monetary inequalities that characterize the Russian society, the population perceives most acutely inequalities in the basic aspects of quality of life - in housing conditions and access to medical care. The author argues that today inequalities are assessed by Russians rather as a social problem that violates a fair social order than as affecting them personally. This complicates the task of reducing inequality on the part of the state, since the population demands not only improving the situation in areas with a high level of inequality but also implementing basic principles of justice in accordance with the normative-value ideas. At the same time, external challenges the country faces partially mitigate the perceived inequality and give the state room to maneuver.